Nutrition transition era: how does nutritional balance of West Sumatra fishermen’s families perform? - Yuliana, Yuliana; Fatimah, Siti; Tasrif, Nabila; Hasanah, Afifah Nur; Harmawan, Violintikha (International Journal of Public Health Science (IJPHS), 2023)
The purpose of this study is to observe the nutritional balance of fisherman's families in the Mandeh area of West Sumatra, Indonesia, in terms of food diversity, a clean and healthy lifestyle, physical activity, and nutritional status during the nutritional transition period. The sample size was 119 fishermen's families from the Mandeh area who were chosen randomly. An interview method that included a questionnaire and anthropometric measurements was used as the data collection technique. The interaction trend of nutritional status with food diversity, a clean and healthy lifestyle, and physical activity was seen by Chi-square analysis. The results found a significant relationship between physical activity and the nutritional status of fishermen's families, with a p-value of 0.020. Meanwhile, there was no correlation between food diversity, a clean and healthy lifestyle, and nutritional status (p>0.05). Additionally, nutritional problems, particularly obesity and malnutrition cases in fishermen's families in the Mandeh area of West Sumatera during the nutritional transition period, require attention; for instance, increasing prevention strategies to maintain nutritional balance.